Development and characterization of topical phyto-formulation for antifungal activity - Choudhury, Ananta; Verma, Reema; Sinha, Devnarayan; Sahu, Saurabh; Roy, Am (Creative Pharma Assent, 2014)
The present study was aimed to develop a potent antifungal topical gel using Curcumin and fluconazole in suitable combination. In these studies we have prepared different gel formulations using polymer like carbapol, Hydroxy propylmethyl cellulose, as well as excepients like tri-ethanolamine, methanol, glycerin and purified water. The formulated gel were evaluated in context of different parameters like drug content, pH, spreadability viscosity , in-vitro drug release , anti-microbial effect etc. Candida albicans was used as a model fungus to evaluate the antifungal activity of the prepared formulations.